Defense Entrepreneurship a Solution to RI Limited Defense Budget - Yulivan, Ivan; Mahroza, Jonni; Rianto, Rianto; Prakoso, Lukman Yudho; Setiadi, Muhammad Ikmal (PT FORMOSA CENDEKIA GLOBAL, 2024)
The vision of a defense budget of 1.5% of gross domestic product (GDP) in 2025 is still difficult to realize. Until 2024, the proportion of Indonesia's defense budget will still be below 1 percent. In addition, the distribution of Indonesia's 2018-2025 defense spending is mostly used for personnel spending and operations and maintenance, followed by the procurement budget. Proficiency in defense entrepreneurship requires risk tolerance, innovation and efficient management; These are important factors for facing changes that will occur in the strategic environment. Using qualitative methodology, this research examines the phenomenon of state problems within the limited state budget for the development of its defense industry. Data was obtained through observation and review of previous research literature. State issues must be reformed in various ways so that various interests and responsibilities can be integrated in order to optimize the state's contribution to the growth of defense entrepreneurship in the defense industry.